2019
DOI: 10.1007/s11218-019-09482-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of group interaction, ethnic group composition, and individual mathematical learning gains

Abstract: High-quality helping behavior is essential for effective peer interaction and learning. This study focused on ethnic group composition and the quality of group interaction as predictors of individual mathematics performance. Video-observations of 92 fifth-grade students working in groups balanced on mathematics performance level were analyzed. We expected a difference in the quality of interaction and test scores of native and non-native students. Multilevel analysis identified process regulation and giving an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Kee (2020) maintained the strong view that interaction is part of the learning experience of adult learners. Further, Mouw et al (2019) also confirmed this theory in 2019, when they investigated the quality of teacher -students' interaction and Mathematical learning gains. They found that there was a positive correlation between teachers' interactions with students and performances in Mathematics.…”
Section: F2f Is Essential For Mathematicsmentioning
confidence: 70%
“…Kee (2020) maintained the strong view that interaction is part of the learning experience of adult learners. Further, Mouw et al (2019) also confirmed this theory in 2019, when they investigated the quality of teacher -students' interaction and Mathematical learning gains. They found that there was a positive correlation between teachers' interactions with students and performances in Mathematics.…”
Section: F2f Is Essential For Mathematicsmentioning
confidence: 70%
“…This category addresses the issue of how instructors should assign learners to collaborative groups. Many collaborative-learning approaches recommend heterogeneous grouping in terms of task-relevant abilities (Cen et al, 2016), gender, and ethnic background (Mouw et al, 2019) to maximize peer-learning opportunities (Webb & Palincsar, 1996), to improve cross-race connections and cross-gender relations, to make groups comparable, and to improve group performance (Anderman & Dawson, 2011;Slavin, 2011; Watanabe, 2012). The benefits of diversity in teams are evident in our interviews.…”
Section: Inputsmentioning
confidence: 99%
“…These processes stimulate cognitive restructuring and enable group members to identify and correct possible flaws or misconceptions in their reasoning (e.g., King, 2002;Webb, 2013). Most studies indeed have found that high-quality helping behaviour can be conducive to individual learning, whereas low-quality helping behaviours such as asking non-specific questions and giving and receiving simple answers are less beneficial (e.g., Webb, Farivar, & Mastergeorge, 2002; for an exception see Mouw, Saab, Janssen, & Vedder, 2019).…”
Section: Establishing Promotive Interactionmentioning
confidence: 99%
“…This is noteworthy because the general assumption is that forming heterogeneous groups augments learning gains as cooperating partners are then stimulated to bring in a variety of skills and knowledge facilitating group discussion (e.g., Baer, 2003). However, this assumption stems from research focusing mostly on cognitive ability levels such as mathematical performance or language proficiency (e.g., Baer, 2003;Cohen, 1994;Mouw, Saab, Janssen, & Vedder, 2019). When group composition is based on group members' social skills such as perspective-taking ability, different processes may come into play.…”
Section: Profiles Of Cooperative Behaviours In Relation To Perspectivmentioning
confidence: 99%